UŻYTKOWANIE WIECZYSTE NIERUCHOMOŚCI KOMUNALNYCH I MOŻLIWOŚCI JEGO PRZEKSZTAŁCENIA W PRAWO WŁASNOŚCI W KONTEKŚCIE DOCHODÓW BUDŻETOWYCH DUŻEGO MIASTA - Kotlińska, Janina (Wydział Prawa i Administracji UAM, 2005)
The institution of a perpetual use has become a vital element of the property management possibilities available in Poland. At the same time it ensures local governments a source of regular revenues, thus securing a stable financial base for budgetary planning. However, since such a form of funding is not very common in the European Union, Polish legislation has been gradually adjusting its solutions to those adopted in other member states. Between 1998 and the end of 2004 the binding regulations in Poland allowed one to transform the perpetual use of property into an ownership title either for a fee (being a price of the property paid at the date of its purchase), or they made property available on preferential basis (by effecting certain prescribed payments), or completely free, for no fee at all. Once this procedure has been stopped, one may expect that the local governments in Poland will eventually lose a significant source of income. So far, however, at least looking at the budget of the City of Poznań, the adverse effects of the new legislation being currently implemented have not been noticed.
PERPETUAL USE OF MUNICIPAL PROPERTY AND POSSIBILITIES OF ITS TRANSFORMATION INTO AN OWNERSHIP TITLE IN THE CONTEXT OF BUDGETARY REVENUES OF A LARGE CITY